ANALISIS SENTIMEN LAPORAN PERKEMBANGAN ANAK DIDIK TAMAN KANAK KANAK DENGAN MENGGUNAKAN METODA NAIVE BAYES - Mina Ismu Rahayu; Fauzi Tsani Zhafran (LPPM STMIK BANDUNG, 2015)
Sentiment analysis or opinion mining is also called, is a field of study in analyzing people's opinion, evaluation, assessment, attitudes and emotions to an entity such as products, services, organizations, individuals, issues, events and topics. Several methods have been applied is Naive Bayes, svm, and K-nn. By using the method of naïve Bayes classification can be found report value contained in how child, with the value of the figure. using naïve Bayes classification is divided into two processes, namely the processes of training and testing. The training process is used to produce a model of sentiment analysis that will be used as a reference to classify sentiment data or the testing of new raw data. Nursery child is early childhood education in the form of formal education. Kindergarten curriculum focused on the provision of educational stimulation to aid growth and development. Students progress report containing narrative value that can be done sentiment analysis to see the intensity of the narration .